Formulasi dan Evaluasi Sabun Cair Cuci Tangan Ekstrak Daun Mint (Mentha piperita) terhadap Bakteri Staphylococcus aureus - Nahdah, Aprilianita Haniyah; Misbakhul Munir; Ita Ainun Jariyah (Biotropic : The Journal of Tropical Biology, 2025)
Soap is a preparation made based on a chemical reaction between sodium and fatty acids. Mint leaves (Mentha piperita) are herbs originating from subtropical regions, with the main ingredients namely menthol, menton, isomenton, piperitone, and methyl acetate. This study aimed to formulate and test the antibacterial activity of mint leaf extract liquid soap against Staphylococcus aureus. The study was conducted using an experimental laboratory with a completely randomized design (CRD) method with mint leaf extract concentrations of 0.01%, 0.02%, 0.04% and 0.08%. Physical evaluation of mint leaf extract liquid soap included organoleptic tests, pH tests, high foam tests, and homogeneity tests. The results on the physical quality test of mint leaf extract liquid soap at concentrations of 0.01%, 0.02%, 0.04% and 0.08% met SNI standards. Antibacterial activity testing of mint leaf extract liquid soap averaged the highest inhibition 0.08%, namely 31.794 mm, is a very strong category. Mint leaf extract liquid soap with the addition of 0.08% extract had the best physical evaluation results and antibacterial activity. This shows that mint leaf extract can be formulated as a liquid soap preparation.